Collagenolytic enzymes from Antarctic hydrobionts: a promising biotechnological approach for accelerating purulent-necrotic wound healing - Raksha, Nataliia; Halenova, Tetiana; Vovk, Tetiana; Koval, Tetiana; Nikitina, Nataliia; Stepanova, Liudmyla; Beregova, Tetyana; Savchuk, Olexiy (Ukrainian Antarctic Journal, 2025)
The objective of this study was to isolate the fractions of proteolytic enzymes from Antarctic hydrobionts, specifically Sterechinus neumayeri and Odontaster validus, and assess their wound-healing potential on purulent-necrotic wounds in rats. The purification procedure included ammonium sulfate precipitation and ion-exchange chromatography on Q-Sepharose. The enzymes derived from both hydrobionts exhibited significant collagenolytic activity, averaging around 14 rel. units per mg of total proteins, and were different in molecular weight and substrate specificity. Enzyme- electrophoresis with gelatin as a substrate revealed that enzymes from S. neumayeri were mostly above 40 kDa, while those from O. validus ranged between 15–35 kDa. The inhibitory analysis demonstrated that O. validus enzymes were predominantly metal-dependent proteases (67%), whereas S. neumayeri contained both serine proteinases (44%) and metal-dependent enzymes (34%). This enzymatic heterogeneity suggests broad substrate specificity, which is advantageous for cleansing various wound types. The enzymes exhibited optimal activity at an alkaline pH (8.0–9.0), which aligns with the pH conditions of chronic and infected wounds, making them particularly effective in the early stages of wound healing. To evaluate the therapeutic potential, a composition based on the mixture of collagenolytic enzymes from both hydrobionts was applied to purulent-necrotic wounds in rats. The group of rats treated with the composition showed faster wound reduction than the control group. By the 12th day, wound size in the treated group had reduced to 24.4 ± 6.7 mm2, significantly smaller than in the control group – 49.8 ± 6.9 mm2. Complete epithelialization occurred by day 27 in the treated group, while the control group achieved full healing by day 30. The results confirm that collagenolytic enzymes from Antarctic hydrobionts are effective in enzymatic debridement, promoting faster wound healing. Combining serine and metal-dependent proteases enhances the range of protein breakdown, improving the efficiency of wound cleansing. The enzymes’ high activity at alkaline pH is beneficial for treating both acute and chronic wounds, with enzyme activity decreasing as healing progresses, minimizing potential damage to healthy tissues.